From Instrument Reform to Systemic Alignment Reform: Comparative Insights from Educational Evaluation Systems in Developed Countries - Ambyah Harjanto; Fitriana Rahmawati; Rabiyatul Andawiyah Siregar; Handoko Handoko (IJLHE: International Journal of Language, Humanities, and Education, 2026)
Educational evaluation has become a central instrument in contemporary educational reform, yet its effectiveness remains uneven across countries despite increasing investments in assessment systems and accountability mechanisms. This study examines educational evaluation systems in Singapore, Finland, Japan, England, Australia, the United States, and Germany from the perspective of educational policy evaluation. Using a qualitative comparative approach based on a Systematic Literature Review (SLR), the study synthesized 34 selected studies and policy documents through the analytical framework of Policy Coherence (PC), System Capacity (SC), and Implementation Fidelity (IF). The findings reveal four distinct educational evaluation typologies: High-Alignment Systems, Trust-Based Adaptive Systems, Accountability-Driven Systems, and Coordinated/Fragmented Hybrid Systems. The analysis demonstrates that educational evaluation effectiveness is not primarily determined by the sophistication of assessment instruments but by the degree of alignment among policy objectives, institutional capacities, and implementation processes. Based on these findings, the study develops the Systemic Alignment Framework and proposes the concept of Systemic Alignment Reform as a new perspective for understanding educational evaluation effectiveness. The study contributes to comparative educational policy scholarship by integrating policy coherence, system capacity, and implementation fidelity into a unified explanatory framework and offers policy insights for strengthening sustainable educational reform across diverse governance contexts.